2008
DOI: 10.1109/tns.2008.920258
|View full text |Cite
|
Sign up to set email alerts
|

Concept Verification of Three-Layer DOI Detectors for Small Animal PET

Abstract: Improved spatial resolution without sacrificing sensitivity is one of the most challenging developmental goals for small animal PET scanners. The 3-layer configuration that we propose here utilizes relative offsets of half a crystal pitch in xand y-directions, and pulse shape discrimination to obtain depth of interaction (DOI). Three layers of crystals with a dimension 1.5 1.5 7.0 mm 3 were composed of a L 0 2 GSO (Lu 0 4 Gd 1 6 SiO 4 : Ce) crystal layer and a L 0 9 GSO (Lu 1 8 Gd 0 2 SiO 4 : Ce) crystal layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…We chose LGSO because it has a fast scintillation decay time (t 5 41 ns), good stopping power (m 5 0.85 cm 21 at 511 keV), and high light output. It has yielded outstanding performance in our previous investigations (18,20), and its MRI compatibility was confirmed (21). The LGSO array consists of 360 (20 · 18) crystals (Supplemental Fig.…”
Section: Pet Detector Modulementioning
confidence: 84%
“…We chose LGSO because it has a fast scintillation decay time (t 5 41 ns), good stopping power (m 5 0.85 cm 21 at 511 keV), and high light output. It has yielded outstanding performance in our previous investigations (18,20), and its MRI compatibility was confirmed (21). The LGSO array consists of 360 (20 · 18) crystals (Supplemental Fig.…”
Section: Pet Detector Modulementioning
confidence: 84%
“…In the LabPET scanner, the PET component of the Triumph pre-clinical SPECT/PET/CT system produced by GE, LYSO and LGSO crystals coupled to APD detectors are employed, and digital signals are sampled using fast free-running ADC and analyzed using an adaptive filtering scheme to discriminate the interaction position [55]. In addition, to the abovementioned commercialized scanners, the feasibility of the pulse shape discrimination method has been confirmed by several other research groups [56,57].…”
Section: Discrete Doi Encodingmentioning
confidence: 96%
“…DOI information can be also obtained using light emitted from the rear surfaces of stacked, optically coupled, multiple crystal blocks [52][53][54][55][56][57]. This method offers cost advantages over the above-mentioned direct readout from crystal layers method, because no additional photo-sensors are required.…”
Section: Discrete Doi Encodingmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve this, several methods to obtain depth of interaction (DOI) information have been proposed [2][3][4][5][6]. In our previous study [7], we demonstrated the feasibility of three-layer depth of interaction (DOI) detectors for a small animal PET using the Monte-Carlo simulation. In this system, three-level DOI encoding was possible due to the relative offset between crystals by one-half a crystal pitch in the x-and y-directions, along with different decay times.…”
Section: Introductionmentioning
confidence: 99%